A COMPREHENSIVE STUDY OF SOCIAL AND ECONOMIC TURMOIL: IMPLICATIONS OF THE PROPOSED 40-75 PERCENT ENTERTAINMENT TAX HIKE IN INDONESIA - Zainal Arifin; Silvia Ekasari; Dinda Ayu Izmi; Fenny Noor Salam; Teguh Prakoso (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This comprehensive study delves into the multifaceted implications of Indonesia's proposed 40-75 percent entertainment tax hike, shedding light on the intricate social and economic landscape it unveils. Focusing on sectors like spas, bars, nightclubs, and karaoke joints, the proposed tax has elicited significant opposition from businesses and workers, triggering concerns about its impact on Indonesia's society. From an economic perspective, spa owners, particularly in Bali, have contested the tax increase, emphasizing potential job losses and economic fallout beyond business owners. The study reveals the profound social implications, emphasizing the threat to financial stability for individuals like Murniyati, a taxi driver dependent on the entertainment sector. Government responsiveness to these concerns, as indicated by a delayed tax hike pending evaluation, reflects a commitment to holistic assessment. Situating the tax within Indonesia's economic policies, the study calls for a balanced approach that considers the interdependencies within the entertainment sector. A legal perspective highlights court challenges, adding a layer of uncertainty for businesses. Regional and demographic differentials, global economic considerations, cultural dimensions, and digital discourse are explored, offering a comprehensive understanding. In exploring societal ramifications, the study considers entertainment services' cultural and social value, emphasizing the need for policies to preserve cultural diversity. The economic landscape is examined for potential ripple effects on employment, and alternative fiscal measures are proposed for a balanced approach. Historical contexts and fairness assessments contribute to a forward- looking perspective.